Traditional Word Guess Game Development âDor-DoranâAs An Integrated Learning Media In The Third Class Of Madiun Islamiyah Islamic Elementary School. - Tryanasari, Dewi (Program Studi S3 Ilmu Pendidikan)
Elementary school children has three main features such as concrete, integrative, and hierarchycal. Untuk memfasilitasi anak belajar sesuai dengan karakteristiknya, perlu rancangan pembelajaran terpadu dan nyata. To facilitate the students to learn accordance with their characteristics, needs to design an integrated learning and real learning. Di kelas III Madrasah Ibtidaiyah Islamiyah Kota Madiun (MIIKM) pembelajaran terpadu telah diterapkan namun kurang menarik.Siswa MIIKM senang bermain. In the third clasa of Madiun Islamiyah Islamic Elementary School (MIIKM) integrated learning has been applied, but less interesting. The students of MIIKM like playing something. Untuk itu media yang bisa digunakan secara langsung dalam pembelajaran adalah permainan âDor-doranâ.thatâs why the media can be used directly in the learning is a game of